2011
DOI: 10.1186/1756-0500-4-534
|View full text |Cite
|
Sign up to set email alerts
|

Variable disease severity in Saudi Arabian and Sudanese families with c.3924 + 2 T > C mutation of LAMA2

Abstract: BackgroundCongenital muscular dystrophy type 1A is caused by mutations in the LAMA2 gene that encodes the laminin α2 chain, a component of the skeletal muscle extracellular matrix protein laminin-211. The clinical spectrum of the disease is more heterogeneous than previously thought, particularly in terms of motor achievement and disease progression. We investigated clinical findings and performed molecular genetic analysis in 3 families from Saudi Arabia and 1 from Sudan in whom congenital muscular dystrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A total of 6 adult CMD patients and 126 adult patients with recessive LGMD are followed in the Neuromuscular Clinic, Rigshospitalet, and all CMD patients were classified diagnostically with either Ullrich myopathy or rigid spine syndrome due to mutations in SEPN1. In the LGMD cohort, 110 of 126 cases were confirmed genetically to be 1 of various subtypes of LGMD; 55 LGMD2I, 16 LGMD2A, 4 LGMD2B, 14 LGMD2L, 10 LGMD2D, 7…”
Section: Lama2-related Muscular Dystrophy In Cohorts Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 6 adult CMD patients and 126 adult patients with recessive LGMD are followed in the Neuromuscular Clinic, Rigshospitalet, and all CMD patients were classified diagnostically with either Ullrich myopathy or rigid spine syndrome due to mutations in SEPN1. In the LGMD cohort, 110 of 126 cases were confirmed genetically to be 1 of various subtypes of LGMD; 55 LGMD2I, 16 LGMD2A, 4 LGMD2B, 14 LGMD2L, 10 LGMD2D, 7…”
Section: Lama2-related Muscular Dystrophy In Cohorts Ofmentioning
confidence: 99%
“…Most children with LAMA2 CMD do not acquire independent ambulation, develop proximal joint contractures and respiratory failure with recurrent chest infections, and the mortality in the first years of life is high . Milder cases of LAMA2 CMD have also been described …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, several studies have reported respiratory insufficiency, feeding difficulties, cardiomyopathy, sensory and motor demyelinating neuropathy, seizure, and external ophthalmoplegia. [ 3 6 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Di Blasi et al . [ 8 ] reported 9 patients with MDC1A from 1 Sudanese and 3 Saudi families. Five of the 9 patients achieved independent walking.…”
Section: Discussionmentioning
confidence: 99%